SHARING IS BEAUTIFUL: AN APPLICATION OF ULTIMATUM GAME - DİLEK, Serkan; KESGİNGÖZ, Hayrettin (Business and Management Studies: An International Journal, 2019)
Economics is a science which is based on decisions of individuals who aims to satisfy their needs. Economic theory which is originated from west is developed by assuming that human makes rational and selfish decisions. Homo economicus individual does not share and interest in only his/her benefits. Ultimatum game is usually used in analysing decision mechanisms of human. This game shows that individual whether prefers selfish choices or fair choices. Researches show that individuals prefer fair alternatives. The aim of this research is to determine preferences of individuals in Turkish society. To this aim we conducted an experiment in students of Kastamonu University Economics and Administrative Sciences. As a result of this research, it is found that individuals are more willing to share and do not act rationally when they think that distribution is not fair.
Keywords: 1. No poverty